Regulamin Papieskiego Kolegium Polskiego w Rzymie z 1866 r. : (cel ustanowienia instytucji, zasady funkcjonowania, personel) - Stępień, Marek (Prawo Kanoniczne, 2011)
In the middle of the XIX century the founders the Congregation of Resurrectionist Fathers started the effort to create the Polish college in Rome. Besides many obstacles, The Pope Pius IX with decree from 9 March 1866 Polish Pontifical College was established in Rome. In the same year the detailed regulation was officially established. The Polish Pontifical College, was the institution acting under the auspices of The Pope Pius IX. Its aim was to prepare the candidates for priestly ordinations and for working on the territory inhabited by the population of Polish nationality. These territories at those times were under the annexation of Russia, Prussia and Austria. The Cardinal Protector watched over the functioning of the College with the assistance of the two deputes, whose duties were caring, observing if the rules of discipline are obeyed and dealing with the current administration of the College. The Rector could be nominated from the group of the priests from the Congregation of Resurrectionist Fathers, which meant the appreciation of the effort put into establishing the college and the role of The Congregation of Resurrectionist Fathers in its creating. The Regulation assumed the possibility of employing the numerous staff, which hierarchically and legally was supervised by the Cardinal Protector and the two priests deputes. Alumni were obliged to study philosophy, theology and law. Regulation of the Polish Pontifical College in 1866 was created according to the pattern of the Papal Regulation of the College Urbano in Rome. The content of these documents was almost identical. The minor differences were connected with the different aims of these institutions as well as the different hierarchical and legal subordinations. It seems that during the time of applying the rules of the Regulation from 1866 Polish Pontifical College fulfilled well the assumed aims and the tasks.